Impact of Artificial Intelligence on New Global Order: A Nepalese Security Perspective - Acharya, GP (Unity Journal, 2024)
The novelty of Artificial Intelligence (AI) and nascent geo-tech interests of powerful countries have largely influenced foreign policy, while ‘techno-geopolitics’ and the emergence of the ‘AI world order’ have constantly challenged the world order milieu. The changing global power dynamics, including the escalating Russia-Ukraine war, the Israel-Palestine conflict and China’s rising clout in tech and diplomatic spheres have induced specific geo-political challenges to the US-led global order. In this context, this research primarily unfolds whether the remaking of new global order can fundamentally be signified by the end of bipolar or unipolar world order, while the advancement of AI technology and geo-tech interests of tech powers have contributed to a remaking of new global order. As the powerful countries have fundamentally concentrated on marshaling AI in foreign policy, both AI and foreign policy have been closely interlinked. This research aims to explore the impact of AI on new global order and corresponding security concerns, particularly Nepalese security concerns. Since both AI and the new global order are relatively vast fields, this research focuses on tech foreign policy that is directly linked with the balance of power and the corresponding international order. This study adopts an analytical descriptive research method. It relates AI ethics and global tech concerns, considering the global need, beginning with the notion of multilateral tech diplomacy, and inquiring whether the tech foreign policy is truly functional. Despite varying challenges to the new global order, rational ‘geopolitical balancing’ and techno-economic cooperation in ‘better-functioning relations’ with immediate neighbors and other superpowers drive Nepal’s security architecture.